Cost effectiveness analysis of parenteral nutrition therapies among hospitalised patients: multi-chamber bag system vs. compounding. (1st January 2014) - Liu, Frank Xiaoqing; Botteman, Marc; Patel, Dipen A.; DeLegge, Mark H.; Mercaldi, Catherine J.; Turpin, Robin S.
Parenteral nutrition (PN) prepared by different methods may be associated with diverse health outcomes and treatment costs. This study used decision analysis techniques to compare the estimated costs of multi-chamber bag (MCB) PN vs. compounded PN in Canadian hospitalised patients in terms of costs and survival rates from the perspective of hospital decision makers. Model inputs were either estimated using the US Premier Perspective™ hospital database and applied to Canadian hospitalised patients or obtained from published literature. Univariate and probabilistic sensitivity analyses were conducted to test the robustness of study results. Compared to compounded PN, MCB PN was estimated to be associated with better outcomes in terms of bacterial infections, including BSI, and patient survival, with lower total hospitalisation costs per patient.